KINERJA SEKRETARIS DESA DALAM PENYELENGGARAAN PEMERINTAHANDESA: STUDI DI DESA CEMPAKA MULIA BARAT KECAMATAN CEMPAGA KABUPATEN KOTAWARINGIN TIMUR - Abdul Hamid (Journal Ilmu Sosial, Politik dan Pemerintahan, 2016)
This study aims to determine the Secretary Of Village performance Cempaka Mulia Barat Village Administration In the Governing Village Cempaka Mulia Barat subdistrict Cempaga District Kotawaringin Timur. The focus of this research study to determine the performance secretary of the village using performance indicators of Anwar Prabu Mangkunegara the quality of work, quantity of work, execution of work and responsibility, as well as factors inhibiting and supporting factors of the performance of the secretary of the village. This research uses descriptive qualitative research method by conducting interviews with the chief, the village secretary, Village Consultative Body, Head of Public Affairs, Head of Government Affairs, Head of Development and Cempaka Mulia Barat Village People. Analysis of data using analytical models Bogdan and Biklen is sifting through the data into units that can be managed, synthesizing the data, search and find data patterns, find important data and learned and decide what can be told to others.